Adaptation of Patient's Colorectal Cancer to Stoma in Padang City - Fira Firdausia; Avit Suchitra; Leni Merdawati (Jurnal Keperawatan, 2021)
Introduction: Colorectal cancer patients have a variety of impacts after the colostomy such as skin irritation, problems with odors, and fears of pouch leaks that will affect daily life. Patients must be able to adapt to new situations due to ostomy so that they can undergo daily activities as usual. This study aims to explore the experience of colorectal cancer patients' adaptation to the ostomy. Materials and Methods: Research was conducted with a qualitative design grounded theory approach with semi-structured interviews on six participants (one man and five women) who were taken purposively with criteria to have an ostomy for more than 4 months at the General Hospital in Padang. After the data is collected, then the data were analyzed using grounded theory by doing open coding, axial coding, and selective coding and determining the core categories. Results: The research obtained the core category of patient’s adaptation to ostomy based on Roy's adaptation theory with two selective codings, among others, the impact of ostomy as a stimulus in patients and coping mechanisms carried out including social support from family, friends, health workers, and ostomates who help patients overcome psychosocial impacts. Conclusion: This study shows the process of ostomate adaptation to the impact of ostomy with various strategies as well as the presence of social support.